An Entropy-Based Computer Model for the Measurement of Phonetic Similarity: Dyslalia Screening in Early School-Age Children - Mahmut, Emilian Erman; Della Ventura, Michele; Stoicu-Tivadar, Vasile (Applied medical informatics, 2018)
This paper presents a computer model for the assessment of the similarity between two sound patterns, to identify phoneme mispronunciations circumscribed by dyslalic disorders in early school-age children (6-10 year olds). From a linguistic standpoint, it is the phonetic tier that is mainly engaged in dyslalia. Unlike other speech disorders, which involve meaning-coding and decoding mechanisms (semantics), dyslalia lends itself more easily to mathematical analysis in the screening stage. The method is based on the analysis of the sound waves and on the quantification of the information carried by every single sound pattern, by calculating its entropy. It is an empirical methodology that provides results that may be analyzed. An experimental study was conducted according to the model and method presented on a sample of 30 subjects. The results are assessed and conclusions are issued. The representation using an isometric diagram accommodates a better interpretation of the results.